The reality of educational activities in the Algerian University - berrek, khadhra; gharbi, khaled (Journal of Social Sciences and Humanities, 2020)
The educational activity is part of the modern educational curriculum, it helps in forming habits, skills, values and methods of thinking necessary to continue education and participate in comprehensive development, so universities today focus on providing diverse opportunities to develop the personality of students that grow only through educational activities, events and partnerships, as well as The students who participate in the activity have the ability to achieve academic achievement, and they are positive for their colleagues and professors, and they have the ability to make decisions, and based on the philosophy of the Ministry of Higher Education and Scientific Research in Algeria to apply the educational system High, educational activities have received considerable attention as part of the main tasks of the University, and these multiple and varied activities, including scientific activities which complement the activities of the scientific aspect of the student in the specialization, which established the concept of scientific thinking. Cultural activities represented in the effort that contributes to the learner acquiring knowledge and information, and social activities that enable students to become familiar with their social duties in the general community. From this standpoint, this study has reached several results that are summarized that the Algerian university has given more attention to scientific activities at the expense of cultural and social activities and that educational activities have an effective role in educational achievement and that the philosophy of educational activity at the Algerian University is based on the positivity of students and its activity and its search for knowledge of its forms Different.